Trabalhador ou bandido? A construção e o conflito de identidades na penitenciária industrial regional de Sobral, Ceará - Sousa, Nelydélia Kelene França de (2008)
The survey, conducted between the years 2006 and 2007, aims to contribute to the understanding of the dynamics of social formation within the existing prisons. The aim of this study is to interpret the process of constructing the identities of prisoners in the prison inmates in the Prison Industrial Regional Sobral (PIRS). This institution, located in the north of the state of Ceara, is part of the prison system outsourced Ceará, managed in partnership by government and by private enterprise: the National Company of Prison Administration (CONAP). The entry of a person in the prison system is described as a rite of passage that will start in the codes and rules specific to the prison society which has belonged. On entering the PIRS, the newly arrested – now will be observed by doctors, psychologists, social workers, lawyers and security guards responsible for giving it a valid identity for the company. The identities assigned to prisoners during the ritual of entry on PIRS are not definitive. The key criterion for the is a constructed identity of the prisoner within that prison society is the participation work in prison. The prison work that produces two groups main identity: the workers and bandits. The relationship between the prisoners belonging to these groups are marked by conflicts expressed in words of namecalling and depreciation, and also by direct physical attacks. In prison, the individual must quickly learn the rules of domestic society and play the role in assigned by their identity prison since it depends largely on its survival in jail.